World history from the ancient world to the information age - Parker, Philip 1965- (New York, New York DK, 2017)
Discover the events that have shaped our world, from the dawn of prehistoric civilization to the digital age, brought to life with contemporary photographs, maps, paintings, and artifacts that place each event in a wider social and historical context
What is history? -- The prehistoric world -- The ancient world -- The classical world -- The medieval world -- The early modern world -- The world of empires -- The modern world
"First American edition published in 2010 as Eyewitness companions world history"--Title page verso
Includes index
1
Keywords: Civilization -- History; Civilization; History, Ancient; History, Ancient; History, Modern; History, Modern; World history; World history; History